Limbic encephalitis and Post-Acute neuropsychology rehabilitation: A review and case examples. Issue 4 (4th July 2022) - Perna, Robert; Arenivas, Ana
Abstract: Rehabilitation research on limbic encephalitis (LE), a rare disorder characterized by inflammation of the brain caused by autoimmunity or infection, has focused on acute rather than post-acute management of symptoms. The frequency of clinical relapse in encephalitis ranges from 12% to 35%. Commonly, individuals diagnosed with LE experience relapses or breakthrough seizures during their post-acute treatment. The treating neuropsychologist will often need to do family and staff education regarding the disorder, possible unusual pattern of recovery and discuss the risk of relapse. Additionally, staff may need help with behavior management and the potential need for a behavior management plan. This manuscript presents a review of these complex issues and reviews how these issues manifest in five individuals who were admitted to a post-acute brain injury rehabilitation program. Only one achieved significant functional gains, as measured by the Mayo Portland Adaptability Inventory(MPAI-4). Each had a low level of functioning on admission with low scores on the Orientation-Log (O-Log) and high scores on the MPAI-4. Relapse involving need for re-admission to an acute setting occurred in four cases and medication side effects (sedation) in three. As a whole, these cases highlight the complex and potentially unusual course of recovery in individuals with LE.